2010
DOI: 10.1186/1475-2840-9-80
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the diagnostic performance of 64-slice computed tomography coronary angiography in diabetic and non-diabetic patients with suspected coronary artery disease

Abstract: BackgroundDiabetics have high prevalence of subclinical coronary artery disease (CAD) with typical characteristics (diffuse disease, large calcifications). Although 64-slice multidetector computed tomography (MDCT) coronary angiography has high diagnostic accuracy to detect CAD, its diagnostic performance in diabetics with suspected CAD is unknown. To compare the diagnostic performance of 64-slice MDCT between diabetics and non-diabetics with suspected CAD scheduled for invasive coronary angiography (ICA).Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…Some studies have shown smaller coronary vessel calibre in patients with T2DM as compared to those without [ 27 , 28 ], and this may affect the diagnostic accuracy of CCTA. Reduced diagnostic performance of CCTA in patients with T2DM is reported in the only known study comparing with patients without T2DM [ 10 ], but this study included mainly symptomatic patients and the prevalence of obstructive CAD was high. On the other side, a mean CAC value of 269 and 18 % patients with zero CAC score would also render CCTA a suboptimal test to rule out obstructive CAD among symptomatic patients [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have shown smaller coronary vessel calibre in patients with T2DM as compared to those without [ 27 , 28 ], and this may affect the diagnostic accuracy of CCTA. Reduced diagnostic performance of CCTA in patients with T2DM is reported in the only known study comparing with patients without T2DM [ 10 ], but this study included mainly symptomatic patients and the prevalence of obstructive CAD was high. On the other side, a mean CAC value of 269 and 18 % patients with zero CAC score would also render CCTA a suboptimal test to rule out obstructive CAD among symptomatic patients [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Coronary computed tomography angiography (CCTA) has over recent years emerged as an alternative to ICA for CAD assessment and the 64-slice generation scanners multidetector computer tomography (MDCT) is now considered to have high diagnostic performance for detection of significant coronary stenosis [ 7 ] in different populations. So far only few studies have assessed the role of MDCT in patients with T2DM [ 8 , 9 ], and its full potential is not fully understood, in particular in light of studies being suggestive of a reduced diagnostic performance of MDCT compared to non-T2DM populations [ 10 ]. Thus, the role of CCTA is considered uncertain in asymptomatic high-risk patients like patients with T2DM [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“… 24 Diagnostic performance of 64-slice CT angiography was significantly reduced in diabetic patients than non-diabetics with similar clinical characteristics. 25 These findings suggest that 64-slice CT angiography could be used for screening CAS in low risk patients. In addition, high radiation exposure is another concern.…”
Section: Discussionmentioning
confidence: 90%
“…Furthermore, all study subjects were enrolled at our healthcare center, not cardiovascular clinic, were not diagnosed with diabetes, did not have a prior history of CAD, and the coronary atherosclerosis was not severe. Therefore, we used SIS (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16) to represent the degree of coronary plaque involvement, and not SSS (1-48), because few subjects had a high SSS. Actually, strong correlations were observed between the SSS, SIS, ABOS and calcium scores ( Supplementary Table 3).…”
Section: Discussionmentioning
confidence: 99%